ASEAN corporate governance scorecard country reports and assessments 2015. (Public private partnership monitor., 2017)
In this fourth edition of the Association of Southeast Asian Nations (ASEAN) Corporate Governance initiative of the Asian Development Bank and the ASEAN Capital Markets Forum, over 500 top publicly listed companies from six ASEAN countries were assessed. In depth analysis of each country including rights of shareholders, equitable treatment of shareholders, role of stakeholders, disclosure and transparency, and responsibilities of the board are discussed.The ASEAN Corporate Governance Scorecard Country Reports and Assessments 2015 is a joint initiative of the ASEAN Capital Markets Forum and the Asian Development Bank.